Protection of Non-Property Right - KHOMENKO, Mykhailo M.; KOSTRUBA, Anatoliy V.; KOT, Oleksii O. (Journal of Advanced Research in Law and Economics, 2019)
In the modern world, the significance of non-property right is very high because they are preconditions of providing the real freedom of ownership, freedom of agreement, freedom of entrepreneurship and all other rights in the material sphere of society. The article studies characteristic features of personal non-property rights of individuals. The notion of personal non-property rights of individuals has been formulated taking into account the features of this group of subjective civil rights, as well as their purpose. The main issues to be addressed in the study are the clarification of the specifics (features) of the object of protection, as well as the peculiarities of the protection of the named rights, the jurisdictional and non-jurisdictional forms of protection of personal non-property rights that ensure the natural existence of an individual. In the article, the notions of personal non-material benefit and personal non-property right have been formulated; the personal non-property rights, which provide the natural existence of an individual who is the object of protection, have been characterised in details; propositions regarding addressing certain legislative and practical gaps and contradictions have been presented. Also, the specific features and concepts of the protection of personal non-property rights that provide the natural existence of an individual have been determined.